1985
DOI: 10.1002/dev.420180606
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in response inhibition and attention in rats rendered mentally retarded by early subcortical brain damage

Abstract: Young rats with lesions to either the globus pallidus, substantia nigra, median raphe, or pontine reticular formation have previously been reported to be deficient in learning a wide variety of laboratory tasks. In the current study, weanling rats subjected to one of these lesions were rested for three weeks, then examined for acquisition and extinction of a water-motivated straight alley task, and finally tested on luminous flux discriminations of increasing difficulty. All brain-damaged groups were slower th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…On the basis of our findings to date, it would appear that the general learning impairment associated with lesions to the GLS in young rats does not arise solely from a defect in response inhibition (Thompson et al, 1989a;Thompson et al, 1985), "voluntary short-term" attentional processes (Thompson et al, 1985), or spatial shortterm "reference" memory (Thompson et al, 1986), working memory (current study). This leaves for consideration the possibility that the relatively broad learning impairment manifested by our brain-damaged rats either is a reflection of some combination of elementary cognitive defects or is a secondary consequence of a disturbance in some superordinate ability (e.g., executive functioning) that transcends the components of cognitive processes.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…On the basis of our findings to date, it would appear that the general learning impairment associated with lesions to the GLS in young rats does not arise solely from a defect in response inhibition (Thompson et al, 1989a;Thompson et al, 1985), "voluntary short-term" attentional processes (Thompson et al, 1985), or spatial shortterm "reference" memory (Thompson et al, 1986), working memory (current study). This leaves for consideration the possibility that the relatively broad learning impairment manifested by our brain-damaged rats either is a reflection of some combination of elementary cognitive defects or is a secondary consequence of a disturbance in some superordinate ability (e.g., executive functioning) that transcends the components of cognitive processes.…”
Section: Discussionsupporting
confidence: 51%
“…So far, our attempts to determine whether GLS-lesioned rats share a common deficit in certain categories of cognitive processes, such as inhibition (as indexed by defective performance on extinction, reversal learning, and passive avoidance), attention (as indexed by impaired performance on visual discriminations of increasing difficulty), or short-term memory (as indexed by inferior leaming under distributed practice as compared with massed practice) have not met with much success (Thompson, Bjelajac, Huestis, Crinella, & Yu, 1989a;Thompson, Harmon, & Yu, 1985;Thompson et al, 1986). Although some of the GLS-lesioned groups showed inhibitory, attentional, or short-term memory deficits, others did not.…”
mentioning
confidence: 99%
“…Aside from frontal regions, empirical work indicates that attentional control is mediated by structures comprising the basal ganglia, including the globus pallidus (Bočková et al, 2011; Muir et al, 1993; Scott et al, 2002), caudate nucleus (Canavero and Fontanella, 1998) and putamen (Max et al, 2002). Moreover, hyperactivation in basal ganglia regions has been reported in rats during attention related tasks (Sotoyama et al, 2011) and lesions to the basal ganglia yield attention deficits both in rats (Muir et al, 1993; Thompson et al, 1985) and humans (Max et al, 2002; Scott et al, 2002). Also, involvement of the globus pallidus and caudate nucleus in attentional control has been demonstrated using electrophysiological recording in Parkinson’s disease (Bočková et al, 2011; Kropotov et al, 1997) as well as in healthy human positron emission tomography studies (Corbetta et al, 1991).…”
Section: Introductionmentioning
confidence: 97%
“…Given that well-defined ''frontal-subcortical loops'' link the basal ganglia to the frontal lobes (Lichter and Cummings, 2001;Middleton and Strick, 2000), subcortical modulation of response inhibition is also posited. One theoretical model has emphasized the role of frontalstriatal connectivity in maintaining inhibitory aspects of cognitive control (Casey et al, 2002), and subcortical lesions have been shown to be sufficient to cause response inhibition deficits in animal models (Thompson et al, 1985). Functional neuroimaging has revealed abnormalities in frontal-striatal blood oxygen level-dependent (BOLD) response in populations with inhibitory deficits, such as fragile X syndrome , Williams syndrome (Mobbs et al, 2006) and attention-deficit hyperactivity disorder (ADHD) (Durston, 2003;Vaidya et al, 2005).…”
mentioning
confidence: 99%